Health Reform: What have we learned and were to next! - David Briggs (ACHSM, 2018)
Recently I was talking to a colleague of mine from Hong Kong and he reminded me that Hong Kong had had 28 years of health reform. A period just slightly longer than we had known each other. We are deeply imbued in the management and organisation of health services and health systems and, therefore public health policy. He suggested that there should be a lot of learning for us all from that period and, he was exploring how that might happen. I agreed with the idea and the need to think it through. I also recognised potential for the Journal to play some role in that suggestion. Most national health systems have undergone extensive reform so there should be a lot of learning for all of us from that reform.....